Synthesis and Antifungal Activity of Pyrimidine Derivatives Containing an Amide Moiety - Wu, Wenneng; Lan, Wenjun; Wu, Chenyan; Fei, Qiang (Frontiers in Chemistry, 2021)
In this study, 17 novel pyrimidine derivatives containing an amide moiety were synthesized. Then their in vitro antifungal activities against Botryosphaeria dothidea (B. dothidea), Phomopsis sp., and Botrytis cinereal (B. cinereal) were determined. Preliminary biological test showed that compounds 5f, 5n, 5o, and 5p exhibited higher antifungal activity against Phomopsis sp., with the inhibition rates of 100%, 91.8%, 100%, and 93.4%, than that of Pyrimethanil (85.1%). Meanwhile, compounds 5f, 5o, and 5p exhibited excellent antifungal activity against Phompsis sp., with the EC50 values of 15.1, 10.5, and 19.6 μg/mL, respectively, which were better than that of Pyrimethanil (32.1 μg/mL).